Voice Behavior as a Mediator: The Effects of Inclusive Leadership and High-Performance Work System on Innovative Behavior at Rakyat Bengkulu Media Group - Nur Afifah Khairani Sheza Cendekia; Praningrum (UPT Jurnal & Publikasi Ilmiah SPs Universitas Ibn Khaldun Bogor, 2025)
This quantitative study aims to investigate the influence of inclusive leadership and high-performance work systems (HPWS) on employees’ innovative behavior, with voice behavior acting as a mediating variable at Rakyat Bengkulu Media Group. The probability sampling method used in this study uses a cluster sampling method and Hair's formula to make sure that there are at least 237 workers in the sample. It was possible to gather information by giving out surveys. Structural Equation Modeling (SEM) research with the SmartPLS 3 software was used to look at the data in this work. The study's results are as follows: (1) inclusive leaership have a positive and significant effect on innovative behavior; (2) high-performance work systems have a positive and significant effect on employee innovative behavior; (3) inclusive leadership has no effect on voice behavior; (4) high-performance work systems have a positive and significant effect on voice behavior; (5) voice behavior has a positive and significant effect on employee innovative behavior; (6) inclusive leadership has no effect on employee innovative behavior with voice behavior as a mediating variable; and (7) high performance work system have a positive and significant effect on employee innovative behavior with voice behavior as a mediating variable. It is expected that the findings of this study will contribute to resolving the challenges encountered by the Rakyat Bengkulu Media Group. The Group’s primary objectives are to address issues related to inclusive leadership, high-performance work systems, and the influence of voice behavior on employee innovation.